Anaerobic toxicity assay of plasticisers - Trzcinski, Antoine P. (2013)
Plasticisers are commonly found in landfill leachate and accumulate in the environment. Some of them are known as disruptive endocrine compound. This manuscript assessed the toxicity of three common plasticisers, including Bis(2-Ethylhexyl)phthalate (DEHP), o-hydroxybiphenyl (HBP) and 2,6-di-tert-butyl-4-(dimethylaminomethyl) phenol (MAMP) on the methanogens during the anaerobic process. It was found that DEHP and MAMP did not impede methanogenesis up to 200 mg/L, but no additional methane could be obtained from their degradation. In contrast, HBP severely inhibited methanogens at 200 mg/L, but after acclimatisation it could be metabolised resulting in a 25% increase in methane production compared to the control.